Dealing with “lived experience”. Benefits and limitations - Zichner, Helga; Happ, Dorit; Bruns, Bettina (ERDKUNDE, 2014)
In this paper we discuss various experiences we have made during fieldwork. Firstly, we will have a closer look at the categories “field” and “place” in general. As the field in our case is derived from a policy approach on the European Union level – a comprehensive political strategy addressed to the neighbouring countries - and as the fieldwork is additionally embedded in a research project drawing on different disciplinary approaches - we clarify in how far the classical notions of “field” and “place” can be applied in our case. After having reconstructed how we can frame sites of our research, we will assume that the process of building rapport between researchers and researched significantly determines the research process and we will reflect on questions of gaining access to the field. Therefore, the analysis will focus on questions of accessibility to the research field and the relationship between the researcher and those being researched, especially focusing on the role that “lived experiences” (BERRY 2011) on both sides may play. Furthermore we analyse our strategic approach working in binational teams to decrease the initial gap between local insiders and us as outsiders and on the other hand deal with a moment of limited access to the field.